Rickettsia parkeri (Rickettsiales: Rickettsiaceae) in the Sky Islands of West Texas. Issue 5 (4th April 2020) - Paddock, Christopher D; Hecht, Joy A; Green, Amy N; Waldrup, Kenneth A; Teel, Pete D; Karpathy, Sandor E; Johnson, Tammi L
Abstract: Rickettsia parkeri, a tick-borne pathogen distributed throughout several countries of the Americas, causes a mild to moderately severe, eschar-associated spotted fever rickettsiosis. Although most U.S. cases of R. parkeri rickettsiosis are reported from southeastern states, some have been reported recently from remote regions of southern Arizona. These cases are linked to R. parkeri -infected ticks of the Amblyomma maculatum (Acari: Ixodidae) group found in several isolated mountain ranges of southern Arizona and New Mexico, referred to as 'sky islands'. Archival records also document ticks of the A. maculatum group collected from domestic and wild animals in West Texas. We surveyed sites in two sky island chains of Jeff Davis and Brewster counties to document the off-host occurrence of these ticks and identify the presence of R. parkeri in the Trans-Pecos region of Texas. During August 2019, 43 adult A. maculatum group ticks were flagged from vegetation or removed from a road-killed, female mule deer. Of 39 samples evaluated by PCR, eight contained a partial sca 0 sequence with complete identity to R. parkeri and two with complete identity to ' Candidatus Rickettsia andeanae', a species of undetermined pathogenicity. Four isolates of R. parkeri were obtained using cell culture. Persons at risk for R. parkeri rickettsiosis include those who work or recreate in these mountains, such as hikers, backpackers, research scientists, foresters, and border enforcement personnel. Additional investigations are needed to define the distribution of these medically important arthropods in other parts of the southwestern United States and northern Mexico.